Mutations and Epidemiology of SARS-CoV-2 Compared to Selected Corona Viruses during the First Six Months of the COVID-19 Pandemic: A Review - Nzivo, Mirriam M.; Budambula, Nancy (My University, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of coronavirus (CoV) disease 2019 (COVID-19). This study compared the genome, mutations, and infectivity/ transmissibility of SARS-CoV-2 with selected betacoronaviruses (beta-CoVs). This study further examined the origin, risk factors, and outbreaks caused by beta-CoVs. We searched the following databases for relevant studies: PubMed, Google Scholar, and the World Health Organization COVID-19 database. A close relationship between SARS-CoV-2 and SARS bat-like CoV RaTG13 (98.9%) was found at the amino acid level, followed by pangolin CoVs. Non-synonymous mutations occur at high frequencies in the open reading frame (ORF) 1ab, spike (S) protein, and nucleocapsid. Mutations P323L and D614G in the RNA-dependent RNA polymerase (RdRp) and S protein, respectively, occur at a high frequency globally. Mutations at position 3037 in the nonstructural protein (Nsp) 3, 14408 (RdRp), and 23403 (S) confer transmissibility to SARS-CoV-2. SARS-CoV-2 has higher infectivity and transmissibility than SARS-CoV, which shares the same receptor. Although bats are confirmed reservoirs, intermediate hosts are currently unknown. Smoking, old age, diabetes, cardiovascular diseases, and hypertension have all been associated with COVID-19. Within six months of its outbreak, COVID-19 was reported in all countries worldwide, whereas SARS was reported in 28 countries and Middle East respiratory syndrome (MERS) in 5 countries. However, the fatality rate of MERS (65%) was higher than that of COVID-19 (4.9%) and SARS (6.6%). Identifying the SARS-CoV-2 intermediate hosts will help prevent future outbreaks. Attention should be given to the pangolin CoVs. Variations in the S gene may confer transmissibility and infectivity.
Keywords: Mutations; SARS-CoV-2; Pandemic; COVID-19; Coronaviruses; Respiratory Syndrome